2007
DOI: 10.1111/j.1525-1594.2007.00440.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Characteristics and Proliferation of Keratocytes Cultured Under Simulated Microgravity

Abstract: This study probed the changes of keratocytes cultured under simulated microgravity. Keratocytes were isolated from rabbit corneas using collagenase digestion method. Cells were seeded in a 55-mL capacity high-aspect-ratio vessel (HARV) of rotary cell culture system (RCCS) at a density of 1 x 10(4) cells/mL. Dehydrated bovine acellular corneal stroma (5 x 5 x 1 mm, n = 30) was used as a carrier for keratocyte culture. Rotational speed was set at 15, 20, and 30 rpm in the first, second, and third week of culture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…This culture system seems to be ideal for overcoming some drawbacks of static culture, because the rotational motion can prevent sedimentation, and create a suspension culture environment and enhance cell-cell interactions. Several researches showed that RCCS contribute to cellular aggregation, intercellular adhesion and formation of 3D cell clumps [18].…”
Section: Introductionmentioning
confidence: 99%
“…This culture system seems to be ideal for overcoming some drawbacks of static culture, because the rotational motion can prevent sedimentation, and create a suspension culture environment and enhance cell-cell interactions. Several researches showed that RCCS contribute to cellular aggregation, intercellular adhesion and formation of 3D cell clumps [18].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, comparison with the static culture, rotating simulated microgravity culture environment can show better cellular vitality and function for some cultivated cells. Our previous study found that SMG cultivation was propitious to proliferation of keratocytes for a rather long period of time [7]. Furthermore, SMG conditions are beneficial to culture stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study showed that bovine acellular stromal lamella appeared in favor of rabbit keratocyte growth in SMG condition. But the preparation process of acellular stromal lamella was rather long time, which underwent the dehydrated procedures of low-temperature preservation in glycerol for 6 months [7]. So, we here adopted short-term chemical-frozen to decellularizate bovine cornea and then prepared them as carriers to culture keratocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jiansu Chen et al. (99) of Jinan University (Guangzhou, China) studied the changes of keratocytes, isolated from rabbit corneas using a collagenase digestion method, cultured under simulated microgravity. Histological evaluations showed that the keratocytes grew into the carriers, but those under conventional gravity grew on the surface of carriers.…”
Section: Tissue Engineeringmentioning
confidence: 99%